A multifunctional thermophilic glycoside hydrolase from Caldicellulosiruptor owensensis with potential applications in production of biofuels and biochemicals. Issue 1 (December 2016) - Peng, Xiaowei; Su, Hong; Mi, Shuofu; Han, Yejun
Abstract Background Thermophilic enzymes have attracted much attention for their advantages of high reaction velocity, exceptional thermostability, and decreased risk of contamination. Exploring efficient thermophilic glycoside hydrolases will accelerate the industrialization of biofuels and biochemicals. Results A multifunctional glycoside hydrolase (GH) CoGH1A, belonging to GH1 family with high activities of β-d -glucosidase, exoglucanase, β-d -xylosidase, β-d -galactosidase, and transgalactosylation, was cloned and expressed from the extremely thermophilic bacteriumCaldicellulosiruptor owensensis. The enzyme exerts excellent thermostability by retaining 100 % activity after 12-h incubation at 75 °C. The catalytic coefficients (k cat /K m ) of the enzyme againstp NP-β-D-galactopyranoside, p NP-β-D-glucopyranoside, p NP-β-D-cellobioside, p NP-β-D-xylopyranoside, and cellobiose were, respectively, 7450.0, 2467.5, 1085.4, 90.9, and 137.3 mM−1 s−1 . When CoGH1A was supplemented at the dosage of 20 Ucellobiose g−1 biomass for hydrolysis of the pretreated corn stover, comparing with the control, the glucose and xylose yields were, respectively, increased 37.9 and 42.1 %, indicating that the enzyme contributed not only for glucose but also for xylose release. The efficiencies of lactose decomposition and synthesis of galactooligosaccharides (GalOS) by CoGH1A were investigated at low (40 g L−1 ) and high (500 g L−1 ) initial lactose concentrations. At low lactose concentration, the time for decomposition of 83 % lactose was 10 min, which is much shorter than the reported 2–10 h for reaching such a decomposition rate. At high lactose concentration, after 50-min catalysis, the GalOS concentration reached 221 g L−1 with a productivity of 265.2 g L−1 h−1 . This productivity is at least 12-fold higher than those reported in literature. Conclusions The multifunctional glycoside hydrolase CoGH1A has high capabilities in saccharification of lignocellulosic biomass, decomposition of lactose, and synthesis of galactooligosaccharides. It is a promising enzyme to be used for bioconversion of carbohydrates in industrial scale. In addition, the results of this study indicate that the extremely thermophilic bacteria are potential resources for screening highly efficient glycoside hydrolases for the production of biofuels and biochemicals.